Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/catal9040347
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Iron Carbides Formed by Iron Oxalate Carburization for Fischer–Tropsch Synthesis

Abstract: Different iron carbides were synthesized from the iron oxalate precursor by varying the CO carburization temperature between 320 and 450 °C. These iron carbides were applied to the high-temperature Fischer–Tropsch synthesis (FTS) without in situ activation treatment directly. The iron oxalate as a precursor was prepared using a solid-state reaction treatment at room temperature. Pure Fe5C2 was formed at a carburization temperature of 320 C, whereas pure Fe3C was formed at 450 °C. Interestingly, at intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…[1][2] Despite the extensive exploration of Fe-based catalysts over the past 90 years, its active phases and reaction mechanisms are still in controversial. 3 The typical iron catalysts, usually produced from thermal reduction and successive activation of iron oxide precursors, contain different phases including metals, oxides and carbides produced during the pretreatment of the catalysts by carbon-containing gases such as CO. [4][5][6][7][8][9][10] The phase evolution of the iron catalysts during FTS reaction is even more complicated, and in most cases, a mixture of different phases was resulted during the FTS reaction. [11][12][13][14][15] To address this issue, various types of metal or metal carbides were prepared.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] Despite the extensive exploration of Fe-based catalysts over the past 90 years, its active phases and reaction mechanisms are still in controversial. 3 The typical iron catalysts, usually produced from thermal reduction and successive activation of iron oxide precursors, contain different phases including metals, oxides and carbides produced during the pretreatment of the catalysts by carbon-containing gases such as CO. [4][5][6][7][8][9][10] The phase evolution of the iron catalysts during FTS reaction is even more complicated, and in most cases, a mixture of different phases was resulted during the FTS reaction. [11][12][13][14][15] To address this issue, various types of metal or metal carbides were prepared.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction result indicated that FeCo/NC-600 catalyst exhibited the highest selectivity of light olefins (C 2 = − C 4 =, 27%) and CO 2 conversion could reach around 37% when this catalyst pyrolyzed at 600 • C in N 2 . The highest selectivity for light olefins may be related to the combination of suitable particle size and sufficient active sites of iron carbide.Catalysts 2020, 10, 455 2 of 17 Fe 5 C 2 are generally deemed as the main active sites for each of these two steps [15,16]. However, the single iron-based catalyst has low catalytic activity and is easy to sinter and deposit carbon.…”
mentioning
confidence: 99%
“…Catalysts 2020, 10, 455 2 of 17 Fe 5 C 2 are generally deemed as the main active sites for each of these two steps [15,16]. However, the single iron-based catalyst has low catalytic activity and is easy to sinter and deposit carbon.…”
mentioning
confidence: 99%
“…The XRD results of MOFs and pyrolysis MOFs are shown in Figure 4A XRD peak of MOF. N at 24° ( Xiong et al, 2015 ) indicates the formation of hematite (Fe 2 O 3 ) with PDF # 33–0664, and at 36°, the formation of iron carbide (Fe 3 C) ( Yang ZhangLiuNingHanLiu et al, 2019 ) with PDF # 00–003–1056 occurs during the preparation. As the MOF is calcined in a tube furnace under the inert nitrogen gas atmosphere, the peak at 29° ( Chun et al, 2014 ) shows the presence of magnetite (Fe 3 O 4 ) with PDF # 19–0770, and the peak at 34.8° indicates the presence of iron carbide (Fe 3 C).…”
Section: Resultsmentioning
confidence: 99%